Control of twin-lift helicopter system - Lye, Cheng Lin. (2010)
The control of a twin-lift helicopter system with and without spreader bar is addressed in this thesis. Fist, the two and three dimensional models of the system are presented. Then three different control schemes are considered; these schemes consist of a PID control law, a robust control law and a variable structure control law. The simulations of the system with the different control laws are carried out using the UH-60 helicopter parameters. The simulations for the spreader bar and the non-spreader bar configurations are discussed. It was found that regardless of the configuration of the twin-lift helicopter system, the variable structure control law achieves better performances than the PID and robust control laws.